CCTV oddity: archaeology and aesthetics of video surveillance. Issue 2 (3rd April 2017) - Cardullo, Paolo
Abstract : The paper narrates #OCTV – an art installation, performance and hacktivist project – the authors presented at the International Visual Sociology Association annual conference (Goldsmiths 2013). The installation used networked CCTV cameras and affordance of digital media to make surveillance space visible, beyond its representational value. It played with the co-constitution of the surveillance images through technologies, cultural practices, and ethics. The paper suggests the visual work of CCTV cameras is contextual to the specific configuration surveillance ecology takes. It proposes art projects as critical methodology for unpacking the social construction of the digital image. As a consequence, it recognises the challenges of using once-upon-a-time ethics forms with regards to ecologies of the visual. Instead, it suggests an ethical and political tension which should follow research 'data' during the lifetime of the project, and possibly in the ecologies yet to come.